Leukotoxin gene and activity in animal and human strains of Fusobacterium species - Tadepalli, Sambasivarao (Kansas State University, 2007)
Fusobacterium necrophorum, a gram negative anaerobe and an opportunistic pathogen, causes necrotic infections in humans and animals. Two subspecies of F. necrophorum, subsp. necrophorum and subsp. funduliforme are described. Leukotoxin (Lkt), a secreted protein encoded by a tricistronic operon (lktBAC), is the major virulence factor of F. necrophorum. The concentration of Lkt produced by subsp. necrophorum is higher than that of subsp. funduliforme. Quantitative-PCR was used to determine the relative expression of lktA by the two subspecies of bovine origin. The mRNA transcript of lktA was detectable in early-log phase of growth in subsp. necrophorum, whereas in subsp. funduliforme, the lktA transcript was detected only in the mid-log phase. Q-PCR analysis revealed that subsp. necrophorum had 20-fold more lktA transcript than subsp. funduliforme. The amount of lktA transcript declined by late-log phase in both subspecies; but lktA mRNA levels in subsp. necrophorum was 8-fold higher than in subsp. funduliforme. Leukotoxin protein stability assays showed the Lkt to be stable in both subspecies despite the decrease in the concentration of the protein during late-log phase. The subspecies identity of human F. necrophorum strains and whether they possess lktA and leukotoxin activity are not known. Human clinical isolates (n = 4) of F. necrophorum were identified as subsp. funduliforme based on 16S rRNA sequence and absence of hemagglutinin gene. Four human strains had the lkt promoter, lktB, and lktC similar to that of subsp. funduliforme. One strain had full length lktA, while other three strains exhibited considerable heterogeneity. All four strains secreted Lkt that was toxic to human leukocytes. Fusobacterium equinum, formerly F. necrophorum, is a newly recognized species. It is associated with infections of the respiratory tract in horses. Little is known about the virulence factors of F. equinum. Southern hybridization revealed that F. equinum strains had lktA gene with greater similarities to F. necrophorum subsp. necrophorum. The toxicity of culture supernatants of isolates to equine leukocytes was variable. Our data indicate that F. equinum isolates possess lktA gene and exhibit leukotoxin activity. The importance of leukotoxin as a virulence factor in human and equine fusobacterial infections needs to be investigated.
Keywords: Fusobacterium necrophorum; lktA; Human strains; leukotoxin operon; Fusobacterium equinum; differential expression; Biology, Microbiology (0410); Biology, Veterinary Science (0778)